TO THE PROBLEM OF INTEGRATION OF EDUCATIONAL, SCIENTIFIC AND SPORTS ACTIVITY IN HIGHER EDUCATION IN THE FIELD OF PHYSICAL CULTURE AND SPORT - Medvedeva, E.N.; Zakrevskaya, N.G.; Solovyov, V.S.; Mikhailova, E.Ya. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to obtain objective data that allow developing evidence-based proposals for the normative, organizational, methodological support of the process of integrating educational, scientific and physical culture and sports activities in higher education in the field of physical culture and sports. Methods and structure of the study. To solve the problems, a set of methods was used to comprehensively and comprehensively study the problem of integration: theoretical analysis and generalization of special literature; retrospective analysis of program and regulatory documents [1-3], retrospective analysis of the direction of dissertation research in the field of physical culture and sports; poll; expert review; testing; modeling; ascertaining experiment; methods of mathematical statistics. Results and conclusions. In the process of analyzing the scientific literature, it was found that the implementation of the integration of education, science and physical culture and sports activities involves: correction of professional and sports training; improving the assessment of types of educational activities; creation of personnel, organizational, logistical and financial conditions; substantiation of normative documents regulating the implementation of this process, etc. Statistical data were obtained on the implementation of the main professional educational training programs, on the organizational, methodological support of the educational process, on the scientific and methodological support of sports teams of various levels. It has been established that at the moment there are integration processes in the system of higher education in the field of physical culture and sports, and the indicators characterizing the effectiveness of educational.